Islamic Finance : Vosviewer Bibliometric Study and Literature Review - Nasser Hasibuan, Abdul; Mayasari Matondang , Desy; H Maydany Pgb , Nurul; Afnita Siregar, Deni; Hardana, Ali (Fakultas Ekonomi dan Bisnis Islam, 2024)
This study reviews research on the theme of Islamic Finance in leading journals. This study uses bibliometric analysis of 186 selected articles related to Islamic Finance published by national and international journals derived from the Dimension database. The entire sample of journal publications has been published in ten years from 2015 to 2024. Based on Author, the research results are dominated by United States and Malaysia, followed by Turkey. Then data processing through analysis using the VosViewer application which aims to determine the bibliometric map of Islamic Finance research development in the world. Furthermore, based on bibliometric keyword mapping, there are 3 clusters that can become research paths with topics related to Islamic Finance. Furthermore, the emergence of Islamic Finance is expected to be able to answer and respond so that the economic traffic of the Islamic community in Indonesia (which the people in Indonesia are Muslims) brings benefits for economic improvement and equitable distribution of people's welfare